Flore Adventices Des Jardins Potagers Des Établissements Pénitentiaires De Côte d’Ivoire: Cas Des Maisons d’Arrêt Et De Correction d’Abidjan Et De Gagnoa - Diomandé Souleymane; Danon Aubin; Amba Achiédo Jean Grévin; Mangara Ali; Bakayoko Adama (European Scientific Journal, ESJ, 2018)
The characterization of the adventitious flora of vegetable gardens consisted of taking inventory of the weedy flora of the plots of prison establishments of the Abidjan Detention and Correction House (ADCH) and the Gagnoa Detention and Correction House(GDCG). The study was carried out using the surface survey method, which consisted of inventory plant species in plots of 100 m2 . 40 weeds species were determined from 144 surveys across the two 2,500 m2 plots. 32 species were identified at ADCH against 39 at GDCH. The inventoried species belong to 14 families divided into 24 genera. The Compositae are in the majority with six species representing 15% of the total adventitious flora. Dicotyledons represent 67.5% of species and 32.5% for Monocotyledons. Therophyte species and herbs are the most dominant with 47.5% and 82.50% respectively.The similarity coefficient (84.3%), being greater than 50%, shows a similarity between the two sites. The study also showed that the most common and aggressive species are Cyperus rotundus L., Euphorbia heterophylla L., and Phyllanthus amarus Schumach. & Thonn. Cyperus rotundus and Panicum repens L. appeared to be the most harmful species.